2021
DOI: 10.1186/s13041-021-00838-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo SCN8A and inherited rare CACNA1H variants associated with severe developmental and epileptic encephalopathy

Abstract: Developmental and epileptic encephalopathies (DEEs) are a group of severe epilepsies that are characterized by seizures and developmental delay. DEEs are primarily attributed to genetic causes and an increasing number of cases have been correlated with variants in ion channel genes. In this study, we report a child with an early severe DEE. Whole exome sequencing showed a de novo heterozygous variant (c.4873–4881 duplication) in the SCN8A gene and an inherited heterozygous variant (c.952G > A) in the CACNA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Stringer and others recently described a patient with epileptic encephalopathy who harbors a de novo heterozygous in-frame duplication in SCN8A (p.G1625_I1627dup) and an inherited heterozygous missense variant in CACNA1H (p.G318S) ( Stringer et al, 2021 ). The p.G1625_I1627dup variant ( Figure 1A , blue circle), located in the DIVS4 transmembrane domain, is proximal to several pathogenic variants, including p.R1620L ( Rossi et al, 2017 ; Liu et al, 2019 ) and p.A1622D ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stringer and others recently described a patient with epileptic encephalopathy who harbors a de novo heterozygous in-frame duplication in SCN8A (p.G1625_I1627dup) and an inherited heterozygous missense variant in CACNA1H (p.G318S) ( Stringer et al, 2021 ). The p.G1625_I1627dup variant ( Figure 1A , blue circle), located in the DIVS4 transmembrane domain, is proximal to several pathogenic variants, including p.R1620L ( Rossi et al, 2017 ; Liu et al, 2019 ) and p.A1622D ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while this duplication does not overlap with the amino acids altered in the ΔIRL and ΔVIR mice, it is immediately adjacent to them ( Figure 1B ). The p.G1625_I1627dup variant resulted in a hyperpolarizing shift of the voltage-dependence of activation of Na v 1.6 but had no effect on sodium current density or gating mechanisms ( Stringer et al, 2021 ). This observation is consistent with a gain-of-function effect on the Na v 1.6 channel; however, Stringer et al also demonstrated that the c.952G > A, p.G318S variant in CACNA1H was associated with loss-of-function effects.…”
Section: Discussionmentioning
confidence: 99%
“…Another homozygous mutation was observed in one individual for a missense mutation in Calcium Voltage-Gated Channel Subunit Alpha1 H (CACNA1H) with three additional individuals also carrying one copy of this mutation. Mutations in this gene have been associated with generalized and severe epilepsies [ 33 , 34 ], although it has been debated whether this is a bona fide monogenic epilepsy gene [ 35 ]. This female individual was diagnosed with epilepsy at 15 years of age and does not have any other family members with a diagnosis of epilepsy, or any consanguinity noted.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an inherited CACNA1H variant has already been reported in worsening a DEE phenotype in association with another gene [ 71 ].…”
Section: Discussionmentioning
confidence: 99%